OBSTRUÇÃO ESOFÁGICA EM LAMA GLAMA: RELATO DE CASO - Thomé, Tainara; Thomas, Lethycia Demczuk; Massa, Isadora Morais; Carneiro, Maico Fernando Wilges; Pinheiro, Fernanda (Anais de Medicina Veterinária; v. 2 n. 1 (2022): 2022/2, 2022)
.